Knowledge and awareness on hepatitis B infection among adult population in some selected villages in Keranigonj, Dhaka, Bangladesh - Shakil, M; Laskar, MS; Farhana, A; Alam, AKMJ; Alam, MAU; Islam, W (Mediscope, 2017)
This cross sectional descriptive study was conducted among the rural people in some selected villages in Keraniganj upazila, Dhaka, Bangladesh from November 2015 to April 2016 to determine the knowledge and awareness about hepatitis B (HB) infection. The sample was collected using non-probability (purposive) method from the available people in the villages. The sample size was 200. The age most of the respondents were in the 26-35 age range; male respondents were higher than that of female and most of the respondents were married. The majority of respondents (60%) had primary and secondary education level, 42% were housewife, 40% had monthly family income range at 5000-10000 Taka, 45% had >5 persons in their family, 51% lived in pacca house, 52.5% drunk water from deep tube-well, and 82.5% did nothing for purification of water and 80% used sanitary latrine. The results of the study revealed that only 43.5% had knowledge on HB and 37.9% knew about HB from doctors. In case of mode of transmission, risk group and prevention of HB, 50.6% thought it is spread by water, 40.2% thought sex workers are more prone to develop HB and only 29% thought HB can be prevented by vaccination. This study indicates that there is a lack of awareness about HB, its route of transmission and modes of prevention among the rural people and appropriate measures are needed to increase correct awareness on HB for prevention purpose. Mediscope Vol. 4, No. 2: Jul 2017, Page 13-19